ChemInform Abstract: Copper Nitrate Mediated Regioselective [2 + 2 + 1] Cyclization of Alkynes with Alkenes: A Cascade Approach to Δ2‐Isoxazolines. Issue 48 (December 2015) - Gao, Mingchun; Li, Yingying; Gan, Yuansheng; Xu, Bin
Abstract: The regioselective synthesis of pharmacologically relevant polysubstituted Δ 2 —isoxazolines is based on the copper‐mediated direct transformation of terminal alkynes and alkenes.